Perception on the role of parenting style on juvenile delinquency among adolescents in the government remand homes, Lagos state Nigeria - Yusuf, Sodiq Adewale; Daud, Mohd Najmi; Arshat, Zarinah (Human Resource Management Academic Research Society, 2021)
Adolescence is a time when juvenile seeks autonomy and develops his own identity. Juvenile delinquency has been a global phenomenon, it has become a major concern of government, parents, schools, and society. To put it into perspective, social scientists agree to classify behaviours against laws and societal norms as delinquent behaviour. The present study examines the role of parenting style on juvenile delinquency, using 170 adolescents with behavioural issues who were place at government remand homes Lagos Nigeria. Simple random sampling was used in selection of the sample. The hypotheses were tested using Pearson correlation at .05 significance level. Results indicate that abusive type of parenting style stands as the main predictor of juvenile delinquency among the adolescent. It is suggested that parent at all levels should step up their parenting effort and adopt authoritative style of parenting as the appropriate style of parenting, based on the research outcome.